Inside Asylum Bureaucracy: Organizing Refugee Status Determination in Austria - Dahlvik, Julia (IMISCOE Research Series, 2018)
Based on a case study on the former Austrian Federal Asylum Agency, the book provides sociological insights on state action in the administration of asylum in a European context. It offers a novel perspective on public administration by complementing the approaches of street-level bureaucracy and organizational sociology with theories of social practice and structuration. The study deals with the working conditions and the working environment as well as with the analysis of the structural differences that characterize the daily work of the decision-makers; the book concludes with a plea for more attention on the topic of ethics in administration, especially in the context of international protection.